Rural Revitalisation Process of Nation-Building in Nepal - Pradhan, Prajwal Man; Jha, Subhash (Nepalese Journal of Development and Rural Studies, 2021)
Government of Nepal has been trying to revitalize rural areas after 1950s as a strategy of nation-building. The demands of ethnic groups are basically inclined with quest for ethnic identity, equality, and greater representation in the political structure. Among the ethnic groups, the largest groups are Janajati, Madhesi and Dalits. In this stance, this library based study tried to look at problems and prospects of balance development as an outcomes of revitalization process of nation-building. At the same time the study also tried to identify essential driver of rural revitalization in Nepali context. The study found that equal distribution of development is difficult in terms of its social, regional and cultural diversity. Poverty, unemployment, landlessness, rapid population is major push factor in Nepal to overcome from this problem. Besides these problems there are some prospects through which rural setting can be revitalized economically, socially, politically such as agriculture. One essential driver of rural revitalization is rurbanomics, an approach that emphasizes the linkages between rural and urban economies. Growing urbanization in most countries enhances the importance of rural areas—by boosting demand for food, diverse diets, and goods and services that the rural economy can meet. Rurbanomics, therefore, frames rural and urban economies as equal partners.Ending hunger and malnutrition to achieve both the Sustainable Development Goals and climate goals requires us to initiate a range of evidence-based actions to advance rural revitalization in all regions of the world. Rural revitalization represents the most realistic way to achieve such a dramatic transformation to ensure that rural people and rural areas can thrive for generations to come.